2013
DOI: 10.1002/oby.20281
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to behavioral targets and treatment attendance during a pediatric weight control trial

Abstract: Better weight loss outcomes are achieved in adults and youth who adhere to obesity treatment regimens (i.e., session attendance and prescribed changes in weight control behaviors). However, more research is needed regarding children’s adherence to a range of behaviors relevant for weight maintenance over long-term follow-up. Overweight children (N=101, aged 7-12 years), along with an overweight parent, participated in a 20-week family-based behavioral weight loss treatment (FBT) and were then assigned to eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 13 publications
1
23
1
Order By: Relevance
“…The current analysis indicates that attendance rates in each of the 3 phases of the TODAY intervention averaged about 60% of the planned sessions; further, more than half of the sample attended 75% or more of the intervention sessions. These rates of attendance are similar to those obtained in other pediatric obesity clinical trials that have focused on youth without diabetes 3‐5 . For example, Kalarchian et al observed an attendance rate of 63% at sessions over a 6‐month period, with ≥75% attendance by 50% of the youth, and attendance was significantly associated with weight loss.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The current analysis indicates that attendance rates in each of the 3 phases of the TODAY intervention averaged about 60% of the planned sessions; further, more than half of the sample attended 75% or more of the intervention sessions. These rates of attendance are similar to those obtained in other pediatric obesity clinical trials that have focused on youth without diabetes 3‐5 . For example, Kalarchian et al observed an attendance rate of 63% at sessions over a 6‐month period, with ≥75% attendance by 50% of the youth, and attendance was significantly associated with weight loss.…”
Section: Discussionsupporting
confidence: 81%
“…Session attendance has been used in several pediatric obesity trials as a proxy for program adherence 3‐5 . The current analysis indicates that attendance rates in each of the 3 phases of the TODAY intervention averaged about 60% of the planned sessions; further, more than half of the sample attended 75% or more of the intervention sessions.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous literature suggests that mean participation rates in family-based prevention and control programs typically range from 59% to 85% and are an important predictor of subsequent changes in program outcomes such as physical activity and BMI. 36-39 Consistent with this literature, a cut-point of approximately 65% was set for differentiating between churches with high vs. low average participation rates. Finally, qualitative data were compared to quantitative assessments of implementation effectiveness to identify church-specific factors most salient to implementation of Faith in Action (see Tables 3 and 4).…”
Section: Methodsmentioning
confidence: 99%